Aspectos da relação entre progresso jurídico e progresso moral na filosofia da história kantiana : uma revisão da literatura - Lima, Cleidson de Oliveira (2021)
The idea that humanity is in constant progress towards the best is the central thesis of the philosophy of Kantian history. For this philosophical thought, progress in history is guided by the establishment and improvement of a legal order, which would lead to the complete development of natural dispositions. Under this perspective, it is possible to understand freedom as an external force, which is linked to human rights, or as internal insights, which are related to the development of moral dispositions, whose sphere is the respect for the moral law. This research aimed to reconstruct and confront the arguments of both interpreters, who either defend the proposal of a moral progress or those who support that of a legal progress. This analysis was carried out by comparing the ideas of these two interpretative currents, in order to verify the unraveling of a tension field inherent to that part of Kant's philosophy. The primacy established for each of the fields by the two groups of commentators ended up diminishing the power of articulation that rights and morals acquire in the Kantian proposal for history.